2021
DOI: 10.3390/jcm10132974
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Severely Worsens Outcome in Patients with COVID-19—A Retrospective Cohort Study from Temporary Critical Care Hospitals

Abstract: Delirium is a sign of deterioration of homeostasis and worse prognosis. The aim of this study was to investigate the frequency, risk factors and prognosis of delirium in patients with COVID-19 in a temporary acute setting hospital. A retrospective cohort analysis of data collected between October 2020 and February 2021 from two temporary acute care hospitals was performed. All consecutive hospitalized patients ≥18 years old with COVID-19 were included. An assessment of consciousness was carried out at least tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The Charlson Comorbidity Index (CCI) was used and calculated using and on-line open-source calculator. Some results from analysis of this database regarding delirium in COVID-19 have already been published [6]. Patients were assessed using the CFS by medical doctors on admission, none of whom were geriatricians, trained according to the recent guidelines [7].…”
Section: Data Pollectionmentioning
confidence: 99%
“…The Charlson Comorbidity Index (CCI) was used and calculated using and on-line open-source calculator. Some results from analysis of this database regarding delirium in COVID-19 have already been published [6]. Patients were assessed using the CFS by medical doctors on admission, none of whom were geriatricians, trained according to the recent guidelines [7].…”
Section: Data Pollectionmentioning
confidence: 99%
“…This is also consistent with available literature; other retrospective studies have found that the presence of delirium is a signi cant predictor of mortality. 7,19,22 Literature is not yet available to support the nding of patients with a combination of cardiac, endocrine, and renal comorbidities on past medical history having a lower risk for mortality. Having comorbidities has been found to be quite common among COVID-19 patients with delirium 7 .…”
Section: Discussionmentioning
confidence: 99%
“…To describe the risk factors, symptomatology, and predictors of mortality of con rmed COVID- 19 Descriptive statistics were used to summarize the demographic and clinical characteristics of the patients. Odds ratio and the corresponding 95% con dence interval were derived from univariate logistic regression.…”
Section: Objectives General Objectivementioning
confidence: 99%
“…There could be a relationship between the administration of medication to control hyperactive ADE and subsequent hypoactivity, causing the mixed and alternate types of hyperactivity and hypoactivity, although in our case, we did not find a statistically significant relationship ( p = 0.09). Although there may be some conflict in the duration of therapy in the following days, its use is recommended for the shortest possible time and at the lowest possible dose [ 5 , 16 , 21 , 35 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%